The Art of Silence: Researching the Role of Silence in Nature Based Expressive Arts - Alexandra Tegart (Art/Research International, 2019)
This paper journeys into the aesthetics of silence in nature-based expressive arts practice and research. Explored is how nature-based expressive arts (EXA) therapy can help cultivate an embodied sense of silence to nourish and support frontline mental health workers in the Vancouver Downtown Eastside, easing the stresses of assisting a population in the midst of an opioid and overdose crisis. The transformational effects of EXA are discussed as they relate to a short series of workshops with frontline mental health workers from Vancouver’s PHS Community Services Society. We collectively experienced how the phenomenon of silence can help provide a rich resource to care providers and, in turn, inform the nature of our research in vulnerable communities.